2018
DOI: 10.1016/j.scib.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Seeing permeability from images: fast prediction with convolutional neural networks

Abstract: Fast prediction of permeability directly from images enabled by image recognition neural networks is a novel pore-scale modeling method that has a great potential. This article presents a framework that includes (1) generation of porous media samples, (2) computation of permeability via fluid dynamics simulations, (3) training of convolutional neural networks (CNN) with simulated data, and (4) validations against simulations. Comparison of machine learning results and the ground truths suggests excellent predi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(87 citation statements)
references
References 32 publications
0
87
0
Order By: Relevance
“…As a complement to rigorous approaches to estimate effective properties from the microstructure, data-driven methodologies to establish structure-property relationships are increasingly being used [43][44][45][46][47][48][49] . The rapid increase in computational resources facilitates the computation of effective properties for very large data sets (hundreds or thousands) of different microstructures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a complement to rigorous approaches to estimate effective properties from the microstructure, data-driven methodologies to establish structure-property relationships are increasingly being used [43][44][45][46][47][48][49] . The rapid increase in computational resources facilitates the computation of effective properties for very large data sets (hundreds or thousands) of different microstructures.…”
mentioning
confidence: 99%
“…Barman et al 46 studied effective diffusivity prediction in 36 virtual porous polymer films using tortuosity and constrictivity. In a different direction, there are several attempts to use 2D and 3D convolutional neural networks (CNNs) to extract information directly from the binary image data describing the structure [47][48][49][51][52][53] in order to predict effective properties. However, these models are usually difficult to interpret and hard to rescale.…”
mentioning
confidence: 99%
“…They found that CNNs demonstrate outstanding performance in predicting the physical parameters of rock if sufficient input data are available. Wu et al [32] predicted the permeability from images when applying CNN and presented a procedure using CNN with simulated data.…”
Section: Previous Studies On the Use Of Cnn In Geosciencesmentioning
confidence: 99%
“…In particular, the quantification of the permeability (PE) of a porous structure has gained attractionowing to its significance in the petroleum industry. In this sake, the stochastic modeling [20] and deep learning strategies have notably been used [21][22][23][24][25][26][27][28] with the latter being applied to the log data as well as the 2D/3D CT-scan images. For stochastic modeling, Eugene et al (2005) [20] applied a combination of lattice Boltzmann method (LBM) and firstorder reliability method (FORM) to construct cumulative distribution functions for randomly-generated porous structures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the deep learning strategy was applied to core data, on a microscopic scale, where processing of the micro-CT images has been on focus. For permeability prediction, Jinlong et al (2018) [25] proposed a physics-informed convolutional neural network approach, which involves a series of fluid dynamics simulations in order to build on the training dataset required. On the other hand, geometrical features in binary segmented images were used by some researchers to estimate permeability, applying multilayer neural network (MNN) and convolutional neural network (CNN) methods [26].…”
Section: Introductionmentioning
confidence: 99%